Use of human growth hormone in treatment of nesidioblastosis in a neonate. Issue 7 (July 1986) - Hocking, M D; Newell, S J; Rayner, P H
Abstract : Growth hormone was effective in reducing the glucose requirement in an infant with nesidioblastosis. He was suffering from fluid overload secondary to glucose and water infusions necessary to maintain blood glucose. Early pancreatectomy is the preferred treatment in severe cases, but human growth hormone has a place in preoperative management.